2019
DOI: 10.1016/j.nbd.2019.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Unit firing and oscillations at seizure onset in epileptic rodents

Abstract: Epileptic seizures result from a variety of pathophysiological processes, evidenced by different electrographic ictal onset patterns, as seen on direct brain recordings. The two most common electrographic patterns of focal ictal onset in patients are hypersynchronous (HYP) and lowvoltage fast (LVF). Whereas LVF ictal onsets were believed to result from disinhibition; based on similarities with absence seizures, focal HYP ictal onsets were believed to result from increased synchronizing inhibition. Recent findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 70 publications
(117 reference statements)
1
9
0
Order By: Relevance
“…Results from the intrahippocampal kainic acid and fluid percussion injury models suggest pathological HFOs could be an electrophysiological biomarker of epileptogenesis. The neuronal mechanisms of epileptogenesis could be due to the formation of PIN clusters 69 . After an episode of status epilepticus or a traumatic brain injury, PIN clusters could form and, through a kindling‐like process, lead to the formation of widespread PIN clusters (Figure 1).…”
Section: Drug‐resistant Epilepsymentioning
confidence: 99%
“…Results from the intrahippocampal kainic acid and fluid percussion injury models suggest pathological HFOs could be an electrophysiological biomarker of epileptogenesis. The neuronal mechanisms of epileptogenesis could be due to the formation of PIN clusters 69 . After an episode of status epilepticus or a traumatic brain injury, PIN clusters could form and, through a kindling‐like process, lead to the formation of widespread PIN clusters (Figure 1).…”
Section: Drug‐resistant Epilepsymentioning
confidence: 99%
“…Investigations have revealed that changes in activities of inhibitory interneurons and excitatory pyramidal neurons contributed to onset and maintenance of TLE seizures. These types of neurons performed different discharge activities and developed distinct oscillatory phases , resulting in distinct seizure patterns . In this study, neural discharges of interneurons and pyramidal neurons were extracted from recorded signals.…”
Section: Resultsmentioning
confidence: 99%
“…), fast rhythmic neocortical busting has been attributed to start spike‐and‐wave discharges in cats (Timofeev & Steriade ), pathologically interconnected bursting neurones were speculated to start hypersynchronous ictal‐onset seizure activity in rodents (Li et al . ) and an increase in bursting propensity has been linked to peritumoural epileptogenic human tissue (Köhling et al . ).…”
Section: What Initiates the Spikes: Principal Busters Or Interneurones?mentioning
confidence: 99%
“…From the 1970s onward, textbook knowledge holds that seizures are initiated by overexcitation; indeed, in many textbooks, the classic figure of Ayala et al (1973) is featured, showing a bursting neurone starting interictal spikes and seizure activity in the penicillin-focus model. Subsequently, an increase in intrinsic hippocampal neuronal bursting has been correlated with post-status epilepticus models in rodents (Chen et al 2011), fast rhythmic neocortical busting has been attributed to start spike-and-wave discharges in cats (Timofeev & Steriade 2004), pathologically interconnected bursting neurones were speculated to start hypersynchronous ictal-onset seizure activity in rodents (Li et al 2019) and an increase in bursting propensity has been linked to peritumoural epileptogenic human tissue (Köhling et al 2006). On the other hand, low-voltage fast Translational Perspectives J Physiol 597.23 ictal onset activity in patients was shown to coincide with a reduction in the firing of large numbers of neurones recorded intracranially (Truccolo et al 2011), along with preserved excitatory-inhibitory connections and sparse firing.…”
Section: What Initiates the Spikes: Principal Busters Or Interneurones?mentioning
confidence: 99%